A new time-domain macromodel for transient simulation of uniform/nonuniform multiconductor transmission-line interconnections - Haque, Monjurul; El-Zein, Ali; Chowdhury, S. (31st Design Automation Conference, 1994)
A rational-function hybrid-parameter model for general multiconductor transmission lines is derived from a spectralmethod solution of the telegrapher equations, using Chebyshev polynomials to represent spatial variation. Time-domain macromodel is then generated by a recursive convolution algorithm which can be simulated efficiently with arbitrary terminations. Results from a transient simulator implementing the approach are presented to demonstrate the accuracy, efficiency and stability of the derived macromodel.